THE EFFECT OF EFFORT-REWARD IMBALANCE ON TURNOVER INTENTION MEDIATED BY BURNOUT AND WORK STRESS IN CONTRACT NURSES - Kurniawaty, Kurniawaty; Tawil, Muhamad Risal (Universitas Brawijaya, Indonesia, 2023)
This paper is motivated by the increasing number of nurse turnover at Bahteramas Hospital over the past 3 years. This incident is caused by factors that cannot be explained. In addition, there are inconsistencies in the findings of previous studies in the effect of effort-reward imbalance on turnover intention where one researcher and another researcher did not reach the same conclusion. This study will examine the model of the effect of effort-reward imbalance on turnover intention by presenting burnout and work stress as mediation. Therefore, this study aims to develop a model to analyze the effect of effort-reward imbalance on turnover intention mediated by burnout and work stress. The study was conducted with a quantitative approach and descriptive design utilizing the conservation of resources (COR) theory paradigm which is proven to be able to overshadow all research constructs. The respondents of the study were contract nurses at the Bahteramas Regional General Hospital in Kendari City, while data collection was carried out with digital instruments in the form of a google form that was distributed and managed to collect a sample of 125 respondents using the Slovin formula which was drawn by simple random sampling. The measurement scale is an ordinal scale. The analysis techniques in this study are descriptive statistics and multivariate analysis with the help of AMOS software.The results of the study proved that mediating variables in the form of burnout and work stress were the main triggers that caused turnover intention in contract nurses at the Bahteramas Regional General Hospital in Kendari City. The implications of this study can be used by hospital management to reduce burnout and work stress of contract nurses so that the presence of turnover intention can be avoided.